Sleep Disturbance Is Associated With the Presence of Portosystemic Collaterals in Patients With Compensated Cirrhosis. Issue 3 (3rd February 2021) - Balakrishnan, Maya; Falker, Caroline; Conley, Samantha; Ciarleglio, Maria; Deng, Yanhong; Redeker, Nancy S.; Garcia‐Tsao, Guadalupe
Abstract : Disturbed sleep is common among patients with cirrhosis. The extent to which this is associated with the different stages of compensated cirrhosis is unknown. This study examines whether the presence of portosystemic collaterals, an indicator of clinically significant portal hypertension, is associated with sleep disturbance in compensated cirrhosis. We conducted a cross‐sectional study among patients with compensated cirrhosis, comparing sleep characteristics, sleep quality, and excessive daytime sleepiness between 21 patients without and 21 patients with portosystemic collaterals. Patients were assessed with wrist actigraphy, Pittsburgh Sleep Quality Index, and the Epworth Sleepiness Scale. Collateral presence was determined by imaging and esophagogastroduodenoscopy. Differences in sleep characteristics were analyzed using t tests and computed effect sizes. Multivariable linear regression analysis was used to evaluate the association between collaterals and sleep disturbance while controlling for possible confounders. The group of patients with collaterals had greater beta‐blocker and tobacco use, lower albumin, and higher international normalized ratio compared to the group without collaterals. Patients with collaterals had more sleep fragmentation (Cohen's d = −0.86), lower sleep efficiency (Cohen's d = 0.59), and lower total sleep time (Cohen's d = 0.75) than patients without collaterals. The presence of collaterals was independently associated with greater sleep fragmentation ( P = 0.046) and greater daytime sleepiness ( P = 0.030). Conclusion: Patients with compensated cirrhosis complicated by portosystemic collaterals experienced more sleep disturbance than those without collaterals.